Estimation of crop evapotranspiration and crop coefficient for coriander using Portable Automatic Closed Canopy Chamber - DEEPAK KUMAR; P.H. RANK (Journal of Agrometeorology, 2023)
An experiment was carried out to determine crop evapotranspiration and crop coefficient of Coriander crop by using Portable Automatic Closed Canopy Chamber (PACCC), Micro-Lysimeter (MLs) and field water balance (FWB) methods. The results revealed that there was no significant difference in the coriander crop evapotranspiration measured by the MLs inside and outside the PACCC and no significant difference among the crop evapotranspiration measured by the PACCC, MLs and FWB at 95 percent confidence level was found. It is indicating that, there are no effects of the change in micro-climate for a short period of 2 minutes in the chamber and on the plant physiological processes. During validation of PACCC, the average crop coefficients measured by MLs were varied from 0.66 to 1.26 for coriander crop. However, the stage wise crop coefficients of corianders measured by FWB were varied from 0.67 to 1.28 during field testing of PACCC. The result showed that the PACCC can be used for measurement of crop evapotranspiration in the field condition.